1999
DOI: 10.1001/jama.281.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Nortriptyline and Interpersonal Psychotherapy as Maintenance Therapies for Recurrent Major Depression

Abstract: LD-AGE DEPRESSION IS WIDEspread, affecting at least 1 in 6 patients in general medical practice and an even higher percentage in hospitals and nursing homes. 1-3 Depression, especially in later life, has serious health consequences, including increased health care costs, 4 increased mortality related to suicide 5 and medical illness, 6,7 and amplification of disability associated with medical and cognitive disorders. 8 A recent study by the World Health Organization concluded that unipolar major depression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
319
1
17

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 598 publications
(351 citation statements)
references
References 30 publications
(8 reference statements)
14
319
1
17
Order By: Relevance
“…Therapy studies have long suggested that maintenance or follow-up sessions are crucial to maintaining positive gains. 27 Future research should examine this therapy within a randomized controlled trial that employs 3-and 6-month follow-up assessments. Such a trial will allow for extensive testing of the risk factor reductions and the associations between changes in patients in a control condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy studies have long suggested that maintenance or follow-up sessions are crucial to maintaining positive gains. 27 Future research should examine this therapy within a randomized controlled trial that employs 3-and 6-month follow-up assessments. Such a trial will allow for extensive testing of the risk factor reductions and the associations between changes in patients in a control condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of treatment for major depression, depressed older adults were randomly assigned to receive nortriptyline, placebo, interpersonal psychotherapy (IPT), or IPT with nortriptyline. In the 3-year follow-up period, the group maintained with combined IPT, and nortriptyline had the lowest recurrence rate (20%) compared with placebo (90%) and was superior in preventing or delaying recurrence [61]. Maintenance treatment is recommended for 12 months after a single episode of depression for older adults and from 1 to 3 years for patients with recurrent depression [62].…”
Section: Maintenance Treatment and Relapse Preventionmentioning
confidence: 99%
“…In a study on elderly patients who had been successfully treated with antidepressants for recurrent depression, the relapse rate in the course of three years of aftercare was 90 % in those who received a placebo, 64 % in those who received interpersonal psychotherapy plus a placebo, 43 % in those who were given nortriptyline and 20 % in those who received nortriptyline plus interpersonal psychotherapy (2).…”
Section: Discussionmentioning
confidence: 99%